GPR120 facilitates cholesterol efflux in macrophages through activation of AMPK signaling pathway. (14th April 2020) - An, Tong; Zhang, Xiaoyi; Li, Hongxia; Dou, Lin; Huang, Xiuqing; Man, Yong; Zhang, Xiyue; Shen, Tao; Li, Guoping; Li, Jian; Tang, Weiqing
Abstract : Cholesterol efflux from macrophages is the initial step of reverse cholesterol transport, an important process for high‐density lipoprotein‐mediated atheroprotection. G protein‐coupled receptor (GPR) 120, which functions as long‐chain fatty acid receptor, is well known for its anti‐inflammatory and insulin‐sensitizing function in macrophages. However, the role of GPR120 on macrophage foam cell formation, the hallmark of atherosclerotic plaques, has not been verified. In this study, we found for the first time that stimulation of GPR120 by its agonist GW9508 elevated the expression of ATP‐binding cassette transporters (ABC) A1 and ABCG1 in THP‐1 macrophage‐derived foam cells and Raw264.7 macrophages, and promoted ABCA1‐ and ABCG1‐mediated cholesterol efflux and reduced cellular cholesteryl ester (CE) content as well. In addition, GPR120 activation was accompanied with the stimulation of AMPK pathway in macrophages; however, the effect of GPR120 on macrophage cholesterol efflux was largely abolished by AMPK inhibition. Moreover, the AMPK activity and the expression of ABCA1 and ABCG1 were markedly abrogated by knockdown of GPR120, or application of phospholipase C (PLC) inhibitor, calcium chelator, or CaMKK inhibitor. Because only free cholesterol can be effluxed from macrophages, we found that activation of AMPK could lead to increase both neutral CEs hydrolysis by upregulation of neutral cholesterol ester hydrolase expression and acid CEs hydrolysis by activation of ULK1. In conclusion, these results demonstrated that GPR120 facilitated ABCA1‐ and ABCG1‐mediated cholesterol efflux through activation of PLC/Ca 2+ /CaMKK/AMPK signaling pathway, which induced CE hydrolysis and elevated the expression of ABCA1 and ABCG1 in macrophages. Abstract : Cholesterol efflux from macrophages is the initial step of reverse cholesterol transport, a process that protects against atherosclerosis by removing cholesterol from the arterial wall. G‐protein‐coupled receptor (GPR) 120 has a poorly defined role in macrophage foam cell formation, the hallmark of atherosclerotic plaques. Here, Weiqing Tang and co‐authors show that stimulation of GPR120 by its agonist GW9508 leads to phosphorylation of AMPK via the PLC/Ca 2+ /CaMMK‐dependent pathway, upregulating the expression of neutral cholesterol ester hydrolase and ATP‐binding cassette transporters ABCA1 and ABCG1. These results show that GPR120 promotes cholesterol ester hydrolysis and ABCA1‐ and ABCG1‐ mediated cholesterol efflux from macrophage foam cells.